Poly‐pharmacokinetic Study of a Multicomponent Herbal Medicine in Healthy Chinese Volunteers. Issue 4 (19th September 2017) - Xie, Guoxiang; Wang, Shouli; Zhang, Hua; Zhao, Aihua; Liu, Jiajian; Ma, Yueming; Lan, Ke; Ni, Yan; Liu, Changxiao; Liu, Ping; Chen, Tianlu; Jia, Wei
Abstract : The advent of mass spectrometry‐based analytical technologies coupled with multivariate statistical methods offer tremendous new opportunities for understanding the pharmacokinetics (PKs) of multicomponent herbal medicines (HMs). We recently proposed a poly‐PK strategy to characterize the concentration‐time profile and the metabolic response profile of multicomponent HMs using an integrated phytochemical and metabolomics approach. Here, we provided the first example of the poly‐PK strategy, in which we simultaneously characterized the PK as well as the metabolic response profiles of a Chinese HM, Huangqi decoction (HQD, consisting of Radix Astragali and Radix Glycyrrhizae ), in healthy Chinese volunteers. Using the poly‐PK approach, we identified 56 HQD‐derived compounds and 292 biotransformed HQD metabolites in human plasma. Additionally, we acquired the concentration‐time profiles of these plasma HQD metabolites and correlated them with a plasma metabolomics profile consisting of 166 human endogenous metabolites that were significantly altered in response to HQD intervention.